OPTIMASI AKURASI DIMENSI HASIL CETAKAN PROSES 3D PRINTING YANG TERBUAT DARI FILAMEN NYLON MENGGUNAKAN METODE TAGUCHI - Inne Dwi Agustini; Hasdiansah Hasdiansah; Adhe Anggry (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Additive manufacturing is a technology for creating real objects directly from CAD models. One of them is 3D printing FDM. The advantages of this technology are that it can print various shapes such as cups and bowls, the material is easy to obtain, low maintenance costs and unattended operation, but it has limitations, one of which is related to the dimensional accuracy of the prints, as a result the resulting product is still not in accordance with the desired design. The final setting of control factors in the optimal FDM 3D printing process is recognized as one of the most important steps to improve product quality. Research on determining the control factors of the Anycubic 4max machine on the bush products made of nylon filament. Varied control factors are nozzle temperature, bed temperature, layer thickness, wall thickness, flowrate, print speed, overlap, infill density, infill speed. Experimental design and optimization using the Taguchi method. The experimental design uses an L27 orthogonal matrix with 3 levels. The results showed that the highest dimensional accuracy was at experimental number 20 with a value of 9.97 mm and the smallest was at experimental number 1 with a value of 9.71 mm. Control factors that affect the FDM 3D printing process, respectively, are layer thickness, nozzle temperature, bed temperature, flowrate, infill speed, overlap, wall thickness, printing speed, and infill density.